Redistribution, Inequality, and Growth - Ostry, Jonathan (Staff Discussion Notes; Staff Discussion Notes ;, 2014)
The Fund has recognized in recent years that one cannot separate issues of economic growth and stability on one hand and equality on the other. Indeed, there is a strong case for considering inequality and an inability to sustain economic growth as two sides of the same coin. Central to the Fund's mandate is providing advice that will enable members' economies to grow on a sustained basis. But the Fund has rightly been cautious about recommending the use of redistributive policies given that such policies may themselves undercut economic efficiency and the prospects for sustained growth (the so-called 'leaky bucket' hypothesis written about by the famous Yale economist Arthur Okun in the 1970s). This SDN follows up the previous SDN on inequality and growth by focusing on the role of redistribution. It finds that, from the perspective of the best available macroeconomic data, there is not a lot of evidence that redistribution has in fact undercut economic growth (except in extreme cases). One should be careful not to assume therefore-as Okun and others have-that there is a big tradeoff between redistribution and growth. The best available macroeconomic data do not support such a conclusion.